Integrating Physical Activity and Gut Microbiota Research in Schizophrenia: A Holistic Health Perspective - Zajkowska, Izabela; Zabrocka, Patrycja; Martowska, Julia; Wojciechowska, Karolina; Baran, Julia; Warych, Wiktor (Quality in Sport, 2025)
Background: Emerging evidence underscores the critical role of the gut–brain axis in schizophrenia, linking microbial dysbiosis not only to neurotransmitter imbalances and neuroinflammation but also to physical performance and overall health status. Given the well-documented benefits of physical activity on brain plasticity and systemic inflammation, investigating its interaction with gut microbiota in schizophrenia patients represents a novel and promising frontier. Aim: This review aims to explore how gut microbiota influence neurotransmitter synthesis and cognitive function in schizophrenia, while highlighting the potential of tailored exercise programs to modulate microbial composition, enhance neuroplasticity, and improve both psychiatric symptoms and physical fitness. Material and Methods: On July 18, 2025, we performed a systematic literature search using a Python-based PubMed scraping tool to gather studies examining the complex relationships among schizophrenia, gut microbiota, neurotransmission, and exercise interventions. Results: Synthesizing findings from clinical and preclinical research, we report that gut microbiota alterations affect key neurochemicals such as serotonin, GABA, and dopamine, while exercise consistently enhances hippocampal volume, cognitive performance, and microbial diversity. These synergistic effects suggest that physical activity may act as a natural modulator of the gut–brain axis in schizophrenia. Conclusions: Integrating exercise therapy with microbiota-targeted interventions offers a promising strategy for improving neurocognitive and physical outcomes in schizophrenia patients. Such multidisciplinary approaches could redefine treatment paradigms by promoting both mental health and physical quality of life.